Depression in Elderly People - Teresa Catarina Paiva; Luísa Soares; Ana Lúcia Faria (Encyclopedia, 2023)
Depression is not a sign of weakness, nor a lack of will or laziness. It is not a simple “being sad” or bored, but rather a pathology that needs intervention, treatment, and monitoring by professionals with expertise in mental health. It is a disorder that impacts the lives of people who do not receive timely help affecting not only the individual himself in his feelings, thoughts, and behaviors but also harming his relationships and daily life and is prevalent among elderly people. Depression manifests through multiple symptoms, is caused by numerous factors, and is preventable with specific practices. It is described as the “most frequent mental health problem worldwide,” has a higher prevalence in women, is different from mourning and sadness, and needs to be addressed to avoid extreme situations, such as suicide.